Social Media and Open Data to Quantify the Effects of Noise on Health - Gasco, Luis; Schifanella, Rossano; Aiello, Luca Maria; Quercia, Daniele; Asensio, Cesar; de Arcas, Guillermo (Frontiers in Sustainable Cities, 2020)
Noise is considered the second threat after air pollution that has an impact on citizens' health and wellbeing in densely populated urban areas, with connections to pathologies of the circulatory and nervous systems such as hypertension. Traditionally, research related to noise in cities was conducted through surveys with a limited temporal and spatial coverage and focused on a subset of the wide spectrum of sound sources present in an urban environment. To overcome these limitations, we resort to geo-referenced social media images to characterize the soundscape of a London at scale. Focusing on health outcomes, we adopt drugs prescriptions data from the UK National Health Service to characterize in space the prevalence of hypertension as a cardiovascular condition potentially linked to sounds exposure. We consistently observe that socioeconomic variables, such as age, gender, and income, play an important role in explaining hypertension rate while official noise exposure levels add a relatively limited contribution in explaining the health outcome. However, our study underlines how the social media powered sonic footprint is, in most use cases, the strongest predictor, incorporating sound sources not considered in the European strategic noise maps. The adoption of these variables shows that the presence of specific types of sounds may influence hypertension more than the noise levels themselves. Connecting the soundscape of an urban area to citizens well-being we provide a tool to support policymakers in designing sensory experiences that have an impact on people quality of life.